A SU-8/PDMS hybrid microfluidic device with integrated optical fibers for online monitoring of lactate. - Wu, M; Cai, H; Xu, X; Urban, J; Cui, Z; Cui, Z (2005)
A microfluidic device with integrated optical fibres was developed for online monitoring of lactate. The device consists of a SU-8 waveguide, microfluidic channels and grooves for the insertion of optic fibres. It was fabricated by one-step photolithography of SU-8 polymer resist. Different channel widths (50-300 microm) were tested in terms of detection sensitivity. A wide range of flow rates were applied to investigate the influence of flow rate on signal fluctuations. The separation between optical fibre sensor and microfluidic channel and the width of fluidic channel have been optimized to maximize the detection sensitivity. It was revealed that 250 microm of channel width is the optimum light path length for a compromise between detection sensitivity and interference of ambient light. The independence of detection signals on flow rates was demonstrated within the range of flow rate (0.5-5 ml/hr) tested. Compared with conventional lactate detection, the device is proved to have high accuracy, relatively low limit of detection (50 mg/L) and reasonably fast response time (100 sec). The fabrication of device is simple and low cost. The present work has provided some fundamental data for further system optimization to meet specific detection requirements.